EFFECT OF POLYMER CONCENTRATION AND SURFACTANTS ON PHYSICAL CHARACTERISTICS, DRUG RELEASE AND ANTIOXIDANT ACTIVITY OF GLUTATHIONE-KAPPA CARRAGEENAN NANOSPHERES: - - NAILUFA, YUYUN; WIDJAJA, BAMBANG (International Journal of Applied Pharmaceutics, 2024)
Objective: Glutathione is one of the antioxidants widely used as an antiaging and skin lightener. Glutathione at a dose of 250 mg/d orally proved useful as an antiaging. At the same time, glutathione topical night cream is effective at a dose of 0.1% for the skin of Indonesian women. Glutathione is one of the antioxidants that has easily oxidized properties in storage. Research purpose to optimize the concentration of kappa carrageenan polymer and surfactan to obtain the optimal physical characteristics of nanosphere system analyzed based on size, PDI, yield, drug loading, entrapment efficiency, dissolution and antioxidant activity. Methods: The most commonly used method of making nanospheres is ionotropic gelation because it has proven effective, easy, and easy to apply. Ionotropic gelation is depend on the tendency of polyelectrolytes to cross connect to develop hydrogel beads often called gelispheres in the existence of counter ions. Nanospheres were prepared by aerosolization ionotropic gelation technique followed by freeze-drying. This method uses carrageenan polymers of 0.5% and 1.0% with the addition of surfactant as a stabilizer. Evaluation parameters are particle size, entrapment efficiency, drug loading, drug release and antioxidant activity. Results: The results of the nanospheres obtained were tested physically and drug activity. Nanospheres successfully formed, with size 382.67±52.24 nm, F2 325.20±4.62 nm, F3 495.39±30.61 nm, and F4 409.80±4.11 nm. The greater the polymer concentration, the greater the value of entrapment efficiency and drug content in the nanosphere. The morphology of the nanosphere is quite good, spherical, with a smooth surface. The release profile shows that glutathione release is quite good but takes a long time, namely F1 73.91±2.17%, F2 75.91±2.76%, F3 78.56±2.82%, and F4 79.56±1.34% in 480 min or 8 h. Antioxidant activity of glutathione-Kappa carrageenan nanospheres with the DPPH method showed that nanospheres have medium or medium category antioxidant activity. Conclusion: The most optimal formula is F4 with 1% kappa-carrageenan concentration and 0.6% KCl.